2022
DOI: 10.3389/fpubh.2022.1064859
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of opportunistic infections in adolescents and adults after the initiation of antiretroviral therapy: A 10-year retrospective cohort study in Ethiopia

Abstract: BackgroundOpportunistic infections (OIs) are the leading cause of morbidity and mortality in people living with the human immunodeficiency virus (PLHIV). However, there are few robust recent data on the rates of OIs and the risk factors that contribute to their occurrence. Therefore, the current study sought to determine the incidence of OIs and identify predictors among adolescents and adults after the initiation of antiretroviral therapy (ART) at Wolaita Sodo University Comprehensive Specialized Hospital (WS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Nevertheless, research reports by Woldegeorgis et al. [ 84 ], and Nicastri et al . [ 85 ] found little evidence for sex differences, which requires a powerful study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, research reports by Woldegeorgis et al. [ 84 ], and Nicastri et al . [ 85 ] found little evidence for sex differences, which requires a powerful study.…”
Section: Discussionmentioning
confidence: 99%
“…Findings in line with our study were reported from India [ 71 , 110 ], and Canada [ 111 ]. A high level of sustained medication adherence is required to suppress viral replication, improve immunological outcomes, decrease OIs, minimize hospitalization and inpatient death, decrease the risk of developing ARV drug resistance, and reduce the risk of transmitting HIV [ 84 , 107 , 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…, etc.) will emergence [ 42 , 43 ], and PLWH do not seek medical attention at hospitals or clinics when they experience symptoms related to OPIs. Instead, they self-medicate or even neglect seeking any treatment, it may exacerbate their condition and increase mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The files provided comprehensive information on HIV status, age, gender, file number, date of admission, residential address, the type of infection presented, appropriate antibiotic therapy administered, and symptoms observed. This data was meticulously organized in Microsoft Excel 2018 to facilitate detailed analysis (7,(19)(20)(21)(22)(23)(24). Following the collection phase, the study encountered the need to exclude 13 patients due to either the lack of specificity regarding the infection or inadequate documentation, resulting in a final sample size of 533 patients.…”
Section: Methodsmentioning
confidence: 99%